Effect of water reservoirs types on the prevalence and antibiotic resistance profiles of Pseudomonas aeruginosa isolated from bathroom water in hospitals - Sri Agung Fitri Kusuma; Tina Rostinawati; Rini Hendriani; Muhammad Faisal Budiman; Ida Parwati (Journal of Advanced Pharmaceutical Technology & Research, 2021)
This study was aimed to isolate and characterize Pseudomonas aeruginosa antibiotic resistance profiles that isolated from bathroom water of five hospitals in Bandung, Indonesia, with different types of water reservoirs. Total of 25 water samples from bathrooms of five hospitals were collected and analyzed for the existence of P. aeruginosa colonies on the surface of MacConkey agar media using a streak plate method and identified using phenotypic identification and a series of biochemical tests. All P. aeruginosa isolates were tested against ceftazidime, piperacillin/tazobactam, ciprofloxacin, meropenem, and gentamicin containing in paper disc, using the agar diffusion method. Of all samples, the total number of P. aeruginosa isolates was less than that of non-P. aeruginosa. In hospitals that use permanent bathtubs, a greater total bacterial count was obtained than those using pails. From 110 isolates, 14.54% were multidrug resistance antibiotics. The majority of the resistant isolates were from hospital B with permanent bathtubs. Of 25 isolates from that hospital, P. aeruginosa isolates were resistant to ceftazidime (20%), piperacillin/tazobactam (4%), ciprofloxacin (20%), and gentamicin (20%). The multiple antibiotic resistance index value of P. aeruginosa isolates was 0.4–0.6. Thus, it can be concluded that the bathroom wáter in the hospital with permanent bathtubs were potential reservoirs of antibiotic-resistant P. aeruginosa.